Differences between male and female players in the frontal plane biomechanics during volleyball spike landing - Chang, C. J.; Chang, J. H.; Huang, C. F. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to investigate differences of kinematic variables between male and female volleyball players after a spiking, to understand the mechanism of volleyball spike landing. Eight males and eight females were recruited to participate in this study from the university volleyball team. The kinematic data were collected by ten Vicon cameras (300Hz) and two force plates (1500Hz). The results presented the right hip joint, and both knee joints are significant differences between male and female volleyball players at initial contact. Similarly, at the moment of peak force during the landing phase, the right hip joint and both knee joints are significant differences between male and female volleyball players. These differences demonstrated that male and female players performed different strategies during volleyball spike landing.